2021
DOI: 10.1364/oe.421019
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of output efficiency of p-face up photonic-crystal surface-emitting lasers

Abstract: We optimized the p-side emission device configuration of photonic-crystal surface-emitting laser (PCSEL) to facilitate the easier chip process and wafer level testing as well as the feasibility of lasing at shorter wavelength. Typically, in order to obtain uniformly distributed current for larger emission area of PCSELs, laser output is designed through the n-side window due to the low hole mobility and thin p-side cladding layer. However, the substrate as well as the epi-layers have to be isolated before the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The cross-sectional views of PCSEL and SEM image of photonic crystal are shown in Figure 6 a and Figure 6 b, respectively. In 2021, Lih-Ren Chen et al also used P-surface ITO deposition to improve the output efficiency of the laser, comparing the slope efficiency of different air hole shapes, and found that increasing the asymmetry of the air hole shape could improve the slope efficiency of the laser [ 54 ].…”
Section: Mode Control Of Vcsel For the Chip-scale Atomic Magnetometermentioning
confidence: 99%
“…The cross-sectional views of PCSEL and SEM image of photonic crystal are shown in Figure 6 a and Figure 6 b, respectively. In 2021, Lih-Ren Chen et al also used P-surface ITO deposition to improve the output efficiency of the laser, comparing the slope efficiency of different air hole shapes, and found that increasing the asymmetry of the air hole shape could improve the slope efficiency of the laser [ 54 ].…”
Section: Mode Control Of Vcsel For the Chip-scale Atomic Magnetometermentioning
confidence: 99%
“…A photonic crystal can be adopted as a lateral laser cavity via monolithic integration embedded in the epitaxial structures, further ameliorating the bulky form factor compared to the laser cavities in VCSEL structures. Laser light emission from such PCSELs exhibits excellent performance, such as a symmetric beam profile with narrow beam divergence and a narrower spectral width than that of VCSELs [36].…”
Section: Introductionmentioning
confidence: 99%
“…GaN-based both optically and electrically pumped PCSELs were demonstrated initially in 2008 [8,9]. PCSELs are candidates to operate as a high-power source with a single mode and narrow divergence angle lasing over a broad area [10][11][12][13][14][15]. Compared with vertical cavity surface-emitting lasers (VCSELs), it does not need the highly reflective Bragg mirror, which is very difficult to implement in a GaN-based material system [16].…”
Section: Introductionmentioning
confidence: 99%